2009
DOI: 10.1007/s00134-009-1424-5
|View full text |Cite
|
Sign up to set email alerts
|

The impact of obesity on outcomes after critical illness: a meta-analysis

Abstract: Obesity is not associated with increased risk for ICU mortality, but may be associated with lower hospital mortality. There is a critical lack of research on how obesity may affect complications of critical illness and patient long-term outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

14
222
7
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 283 publications
(245 citation statements)
references
References 51 publications
14
222
7
2
Order By: Relevance
“…Similar to inconsistent relationship mortality and MV, the data for ICU and hospital LOS varies as well. Some studies reports a higher ICU and hospital LOS across all BMI groups [20,23] while others reports no correlation [17]. In our study although the Hospital LOS were similar between BMI groups, The ICU LOS was higher in severely obese patients.…”
Section: Icu Los (Mean ± Sd)contrasting
confidence: 57%
See 1 more Smart Citation
“…Similar to inconsistent relationship mortality and MV, the data for ICU and hospital LOS varies as well. Some studies reports a higher ICU and hospital LOS across all BMI groups [20,23] while others reports no correlation [17]. In our study although the Hospital LOS were similar between BMI groups, The ICU LOS was higher in severely obese patients.…”
Section: Icu Los (Mean ± Sd)contrasting
confidence: 57%
“…Population based studies suggest a U or J shaped curve indicating a higher mortality at the extremes of BMIs [8][9][10]. The association of BMI with mortality in the intensive care unit (ICU) is controversial with reports suggesting no relation [11][12][13], increased [14][15][16] or decreased hospital mortality [17]. The role of BMI for length of stay (LOS) on mechanical ventilation (MV) and ICU LOS is equally inconsistent [11,[18][19][20][21][22][23].…”
Section: Introductionmentioning
confidence: 99%
“…However, the impact of obesity on outcomes in patients admitted to the ICU has not been definitively determined. Although 3 meta-analyses [12][13][14] regarding the impact of obesity on outcomes in critically ill subjects showed that obesity might exert a favorable effect on mortality, definitive SEE THE RELATED EDITORIAL ON PAGE 1083 conclusions have not been available due to statistical heterogeneity. A recent Dutch study 15 including Ͼ 150,000 subjects demonstrated a paradoxical relationship, with a higher BMI associated with a lower mortality in critically ill subjects.…”
Section: Introductionmentioning
confidence: 99%
“…7 On the other hand, a meta-analysis published in 2009 indicated that hospitalized, acutely ill, obese patients were protected from poor outcomes. 8 This meta-analysis included a total of 88,051 obese and non-obese patients from 22 studies. Mortality of obese patients was statistically lower than in patients who were not obese.…”
Section: Introductionmentioning
confidence: 99%